Exergy Based Performance Analysis Of Double Flow Solar Air Heater With Corrugated Absorber - S. P. Sharma; Saha, Som Nath (Zenodo, 2017)
This paper presents the performance, based on exergy analysis of double flow solar air heaters with corrugated and flat plate absorber. A mathematical model of double flow solar air heater based on energy balance equations has been presented and the results obtained have been compared with that of a conventional flat-plate solar air heater. The double flow corrugated absorber solar air heater performs thermally better than the flat plate double flow and conventional flat-plate solar air heater under same operating conditions. However, the corrugated absorber leads to higher pressure drop thereby increasing pumping power. The results revealed that the energy and exergy efficiencies of double flow corrugated absorber solar air heater is much higher than conventional solar air heater with the concept involving of increase in heat transfer surface area and turbulence in air flow. The results indicate that the energy efficiency increases, however, exergy efficiency decreases with increase in mass flow rate. : {"references": ["Wenxian Lin, Wenfeng Gao and Tao Liu, \"A parametric study on the thermal performance of cross-corrugated solar air collectors,\" Applied Thermal Engineering, vol. 26, pp. 1043-1053, 2006.", "Goldstein, L. and Sparrow, E.M., \"Experiments on the transfer characteristics of a corrugated fin and tube heat exchanger configuration,\" Transaction of the ASME, Journal of Heat Transfer, vol. 98, pp. 26-34, 1976.", "Akpinar Ebru Kavak and Kocyigit Fatih, \"Energy and exergy analysis of a new flat-plate solar air heater having different obstacles on absorber plates,\" Applied Energy, vol. 87, pp. 3438-3450, 2010.", "Abhishek Priyam, Prabha Chand and Suresh Prasad Sharma, \"Energy and exergy analysis of wavy finned absorber solar air heater,\" International Energy Journal, vol. 16, pp. 119-130, 2016.", "Sahu Mukesh Kumar and Prasad Radha Krishna, \"Exergy based performance evaluation of solar air heater with arc-shaped wire roughened absorber plate,\" Renewable Energy, vol. 96, pp. 233-243, 2016.", "Mahdi Hedayatizadeh, Faramarz Sarhaddi, Ali Safavinejad, Faramarz Ranjbar and Hossein Chaji, \"Exergy loss-based efficiency optimization of a double-pass/glazed v-corrugated plate solar air heater,\" Energy, vol. 94, pp. 799-810, 2016.", "Bahrehmand, D., Ameri M. and Gholampour, M., \"Energy and exergy analysis of different solar air collector systems with forced convection,\" Renewable Energy, vol. 83, pp. 1119-1130, 2015.", "Huseyin Benli, \"Experimentally derived efficiency and exergy analysis of a new solar air heater having different surface shapes,\" Renewable Energy, vol. 50, pp. 58-67, 2013.", "Lalji, M.K., Sarviya, R.M., and Bhagoria, J.L., \"Exergy evaluation of packed bed solar air heater,\" Renewable and Sustainable Energy Reviews, vol. 16, pp. 6262-67, 2012.\n[10]\tGupta, M.K. and Kaushik, S.C., \"Performance evaluation of solar air heater for various artificial roughness geometries based on energy, effective and exergy efficiencies,\" Renewable Energy, vol. 34, pp. 465-476, 2009.\n[11]\tHikmet Esen, \"Experimental energy and exergy analysis of a double-flow solar air heater having different obstacles on absorber plates,\" Building and Environment, vol. 43, pp. 1046-1054, 2008.\n[12]\tSalwa Bouadila, Mariem Lazaar, Safa Skouri, Sami Kooli and Abdelhamid Farhat, \"Energy and exergy analysis of a new solar air heater with latent storage energy,\" Int J Hydrogen Energy, vol. 39(27), pp. 15266-74, 2014.\n[13]\tSaha. S.N., and Sharma S.P., \"Analysis of thermohydraulic performance of double flow v-corrugated absorber solar air heater,\" International Energy Journal, vol. 16, pp. 131-142, 2016.\n[14]\tKlein, S.A., \"Calculation of flat plate loss coefficients,\" Solar energy, vol. 17, pp. 79-80, 1975.\n[15]\tMcAdams, W.H., Heat transmission. New York: McGraw-Hill, 1954.\n[16]\tHottel, H.C. and Woertz, B.B., \"Performance of flat plate solar heat collectors,\" Trans ASME, vol. 64, pp. 91-104, 1942.\n[17]\tKarim, M.A., Perez, E. and Amin, Z.M., \"Mathematical modelling of counter flow v-grove solar air collector, Renewable Energy, vol. 67, pp. 192-201, 2014.\n[18]\tHollands, K.G.T. and Shewen, E.C., \"Optimization of flow passage geometry for air heating plate type solar collectors,\" ASME J Solar Energy Eng, vol. 103, pp. 323-30, 1981.\n[19]\tHeaton, H.S., Reynolds, Wc. and Kays, W.M., \"Heat transfer in annular passages. Simultaneous development of velocity and temperature fields in laminar flow,\" Int J Heat Mass Transfer, vol. 7, pp. 763-81, 1964.\n[20]\tKays, W.M., Convective heat and mass transfer. New York: McGraw Hill, 1980.\n[21]\tEl-Sebaii, A.A., Aboul-Enein, S., Ramadan, M.R.I., Shalaby, S.M. and Moharram, B.M.., \"Investigation of thermal performance of double pass flat and v-corrugated plate solar air heaters,\" Energy, vol. 36, pp. 1076-1086, 2011.\n[22]\tHegazy, A.A., \"Thermohydraulic performance of air heating solar collectors with variable width, flat absorber plates,\" Energy Convers Manage, vol. 41, pp. 1361-78, 2000.\n[23]\tGriggs, E.I. and Sharifabad, F.K., \"Flow characteristics in rectangular ducts,\" ASHRAE Trans, vol. 98(1), pp. 116-27, 1992."]}